1999
DOI: 10.1258/0956462991914177
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Delay and Reliance on Private Physicians among Patients with Sexually Transmitted Diseases in China

Abstract: We examined health-care seeking practices among patients with sexually transmitted diseases (STDs) in south China. In 1995, we recruited a consecutive sample of 939 STD patients attending the STD clinics of the Municipal STD Control Centers of Guangzhou and Shenzhen, 'special economic zones' near Hong Kong. Attending physicians interviewed patients face-to-face using a standard survey questionnaire. Twenty-seven per cent of all subjects had sought treatment elsewhere for their presenting complaints, before vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 14 publications
(15 reference statements)
0
19
1
Order By: Relevance
“…2 Although STIs can cause significant morbidity, treatments for STIs in China often were inadequate. 3 Chinese STI patients often relied on private unlicensed physicians rather than formally trained doctors in public hospitals because of stigma associated with public venues. 4 At the same time, education was found to be inversely related to STI prevalence in both men and women in China.…”
mentioning
confidence: 99%
“…2 Although STIs can cause significant morbidity, treatments for STIs in China often were inadequate. 3 Chinese STI patients often relied on private unlicensed physicians rather than formally trained doctors in public hospitals because of stigma associated with public venues. 4 At the same time, education was found to be inversely related to STI prevalence in both men and women in China.…”
mentioning
confidence: 99%
“…Patients may choose to see private physicians rather than a public practitioner for reasons of confidentiality, convenience, shorter waiting times, or better service (perceived or actual), among other reasons (26,27). Although patients may believe that better care is provided in private settings, the opposite may be true in the case of STIs, given that private physicians for the most part do not receive regular training, whereas in the public sector there are multiple efforts to train health personnel.…”
Section: Sexually Transmitted Infections and Private Physiciansmentioning
confidence: 99%
“…However, little effort has been focused on promoting appropriate health-seeking behaviors or assessing the availability and use of existing STD services. 9 Misconceptions regarding appropriate STD treatments are common. 10 The stigma of being identified as an STD patient and the prejudicial attitude among health providers inhibits use of public clinics.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 According to Choi et al, 9 the main sources of STD treatments among their study participants were private physicians followed by public clinics and drugstores and factors associated with treatment-seeking behaviors differed by gender. Zhao et al 8 identified pharmacies as the most common source of treatment.…”
Section: Introductionmentioning
confidence: 99%